PENGARUH PERUBAHAN VARIASI DIMENSI KOLOM TERHADAP KEKUATAN STRUKTUR BANGUNAN TINGGI PADA PROYEK ANTASARI PLACE. - Rivaldi, Fandhy (Universitas Negeri Surabaya, 2023)
Indonesia has many high-rise buildings for residential, office, and others. Indonesia is a country that has experienced many natural disasters such as earthquakes which have an impact on the structural strength of buildings, especially high-rise buildings. This research was conducted to determine the variations in the dimensions of the structural column sizes in a building that affect the strength of the building structure when reacting to an earthquake assisted by using the SAP2000 V14 software. The method used in this study is by using modeling analysis using SAP2000 software. The results of the research on changes in column dimensions on the strength of tall building structures affect displacement that occurs due to earthquakes, where the variation of column dimensions is 6 times, the smaller the displacement value of the building and the more axial force values ??that the building structure can accept so that the building becomes better. conversely, in the variation of the column dimensions with 4 changes, the value obtained at the displacement is greater and the value of the axial force that can be accepted by the structure is smaller so that the strength of the structure in the building is getting worse.